Predicting Haze Stability in Wheat Beer using Light Scattering Analysis Techniques - Schwarz, Cem; Zarnkow, Martin; Back, Werner; Becker, Thomas (BrewingScience, 2011)
Visible and intense turbidity is seen as a defining characteristic of German and Belgian wheat beers. To date, no reliable method has been established for predicting the haze stability of wheat beer. It would be very beneficial for breweries to be able to predict haze stability so as to ensure that the beer retained a satisfactory level of haze during its shelf life. To predict wheat beer haze, trials were undertaken, in which light scattering analysis techniques and particle size distribution measurements were made, for the purpose of characterizing the haze stability of wheat beer. The wheat beer samples assessed had substantial differences in haze stability durability, from 19 days up to more than 160 days, as judged by when 90° scatter light intensity drops bellow 30 EBC units. Interestingly, the classification of all samples by the 90°:25° ratio of scatter light intensity showed values from 0.5 up to 1.0 and it was observed that as haze stability increases, the ratio expressing the intensity of light scattering at 90°:25° also increases. Particle size distribution measurements showed for samples with high 90°:25° ratios of scatter light intensity (>0.9) had monomodal distributions with high ratios of particles < 1 μm which was favourable indicator of beer haze durability* .